Maternal and child health services and an integrated, life-cycle approach to the prevention of non-communicable diseases. Issue 3 (19th August 2017) - Brumana, Luisa; Arroyo, Alvaro; Schwalbe, Nina R; Lehtimaki, Susanna; Hipgrave, David B
Abstract : Described as the 'invisible epidemic', non-communicable diseases (NCDs) are the world's leading cause of death. Most are caused by preventable factors, including poor diet, tobacco use, harmful use of alcohol and physical inactivity. Diabetes, cancer and cardiovascular and chronic lung diseases were responsible for 38 million (68%) of global deaths in 2012. Since 1990, proportionate NCD mortality has increased substantially as populations have aged and communicable diseases decline. The majority of NCD deaths, especially premature NCD deaths (<70 years, 82%), occur in low-income and middle-income countries, and among poor communities within them. Addressing NCDs is recognised as central to the post-2015 agenda; accordingly, NCDs have a specific objective and target in the Sustainable Development Goals. While deaths from NCDs occur mainly in adulthood, many have their origins in early life, including through epigenetic mechanisms operating before conception. Good nutrition before conception and interventions aimed at preventing NCDs during the first 1000 days (from conception to age 2 years), childhood and adolescence may be more cost-effective than managing established NCDs in later life with costly tests and drugs. Following a life-course approach, maternal and child health interventions, before delivery and during childhood and adolescence, can prevent NCDs and should influence global health and socioeconomic development. This paper describes how such an approach may be pursued, including through the engagement of non-health sectors. It also emphasises evaluating and documenting related initiatives to underwrite systematic and evidence-based cross-sectoral engagement on NCD prevention in the future.